2018
DOI: 10.1186/s12865-018-0249-9
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic cancer vaccine: phase I clinical tolerance study of Hu-rhEGF-rP64k/Mont in patients with newly diagnosed advanced non-small cell lung cancer

Abstract: BackgroundHu-rhEGF-rP64k/Mont is a biotechnology product for the treatment of advanced non-small cell lung cancer (NSCLC). The vaccine induces a neutralizing antibody-mediated immune response, against the normal circulating self-protein antigen epidermal growth factor (EGF), which prevents its binding to and activation of the EGF receptor, inhibiting the transduction of the signals that drive cancer cell proliferation, survival and spread. This phase I study aimed to evaluate the safety and the immunological r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…Over the past five years (2017-2021), 15 lung cancer vaccine research projects have been reported worldwide [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Most of the projects are in Phase I to II trials, only one is in the experimental development phase and the other is in the improvement phase.…”
Section: Current Research Progress Of Vaccine Immunotherapy For Nsclcmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past five years (2017-2021), 15 lung cancer vaccine research projects have been reported worldwide [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Most of the projects are in Phase I to II trials, only one is in the experimental development phase and the other is in the improvement phase.…”
Section: Current Research Progress Of Vaccine Immunotherapy For Nsclcmentioning
confidence: 99%
“…In this experiment, 14 cases (66.67% of 48 cases) reported adverse events, mainly in grade I/II, and 1 case in grade III. The researchers believe that the adverse reactions in some of these cases may be related to previous chemotherapy [33]. Another phase I trial of intratumoural injection of autologous DC (AdCCL21-DC) overexpressing CCL21 found that influenza-like symptoms and bloody sputum, nausea and fatigue were common symptoms.…”
Section: Adverse Reactions Of Vaccine Immunotherapy For Nsclcmentioning
confidence: 99%
“…However, patients with NSCLC lacking driver mutations do not benefit from targeted therapies (20,21). ICIs, adoptive T cell therapies, cytokineinduced killer cells, and other emerging immunotherapies are transforming the treatment of NSCLC, especially those lacking driver mutations (9,(22)(23)(24)(25)(26).…”
Section: Standard Nsclc Treatmentmentioning
confidence: 99%
“…In the last decades, multiple vaccination strategies have been developed for lung cancer patients (Table 1). [21][22][23][24][25][26][27][28][29][30]32,[34][35][36][37][38][39][40] However, modest clinical outcomes, complex manufacturing processes, and the recent advent immune checkpoint blockers have limited their clinical impact. Modern personalized neoepitope-based strategies 31,33 and combination with checkpoint blockers might reactivate this therapeutic modality in the future.…”
Section: Vaccinesmentioning
confidence: 99%